Pembelajaran Aswaja Sebagai Implementasi Pendidikan Akhlak - Budiyono , Ahmad; Mulyadi, Andri; Adi Wijono , Hani (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Education is the process of educating, nurturing, and shaping students to have noble character and intellectual intelligence. Character education plays an important role in the Indonesian education curriculum, especially in the development of Islamic teachings as reflected in the Nahdlatul Ulama (NU) Constitution. This study aims to determine the planning, implementation, and evaluation of Aswaja learning as moral education at El Wahid Tembelang Islamic Elementary School in Jombang. This study uses a qualitative method with a descriptive design through field research, with data in the form of spoken and written words from observations, interviews, and documentation. The results of the study indicate that Aswaja learning is a form of synergy between the local content of the Jombang Regency Education Office and school policy. The planning of learning refers to the established Competency Standards and Basic Competencies. The implementation of learning is carried out inside and outside the classroom through practical activities. Learning evaluation is carried out continuously through weekly tests, Mid-Semester Assessments (PTS), and Final Semester Assessments (PAS).